Emotion sensitivity and self‐reported symptoms of generalized anxiety disorder across the lifespan: A population‐based sample approach. Issue 6 (16th April 2019) - Rutter, Lauren A.; Scheuer, Luke; Vahia, Ipsit V.; Forester, Brent P.; Smoller, Jordan W.; Germine, Laura
Abstract: Background: Individuals with generalized anxiety disorder (GAD) symptoms show deficits in emotion processing, but results of prior studies have been conflicting, and little is known about developmental trajectories of emotion processing over time. We examined the association between GAD symptoms and sensitivity to recognizing emotional facial expressions (emotion sensitivity: ES) for three emotions (happiness, anger, fear) in a large, diverse, population‐based sample. We hypothesized that higher anxiety scores would be associated with poorer performance, and expected that ES performance and anxiety scores would decline across the lifespan. Method: Participants were 7, 176 responders to a web‐based ES study (age range = 10–96 years old). Results: Higher GAD‐7 scores were associated with poorer ES performance for all emotion categories (happiness, anger, fear). The relationship between GAD‐7 and ES scores remained significant after controlling for the effects of age and sex, and there was no significant interaction, indicating that the relationship does not change across age. Age significantly predicted ES and GAD‐7 scores across emotions, with older ages showing lower ES scores and lower anxiety. Conclusions: In the largest study of its kind, GAD symptoms were associated with impaired ES performance across three emotion types. Future research should explore the connection between anxiety symptoms, cognitive processing, and social processing to better characterize the mechanisms of how GAD is linked with both social and non‐social information processing. Future work may also look at if ES is related over time to changes in anxiety, making it a promising target for intervention. Abstract : Higher generalized anxiety disorder (GAD)‐7 scores were associated with poorer emotion sensitivity (ES) performance for all emotion categories (happiness, anger, fear). The relationship between GAD‐7 and ES scores remained significant after controlling for the effects of age and sex, and there was no significant interaction, indicating that the relationship does not change across age. Age significantly predicted ES and GAD‐7 scores across emotions, with older ages showing lower ES scores and lower anxiety.